Aggressive children and adolescents (Journal of Parents and Teachers, 2017)
The article describes the aggressiveness in children and adolescents analyzing their conceptualization, different typology and forms, as well as its assessment and theoretical models that allow us understanding why our children can become aggressive. From these approaches, we highlight a series of different strategies that allow us to reduce and control the aggressiveness of children in school and family contexts.
Keywords: aggression; children; scholar context; family